Poverty in Perspective of Christian Faith by Congregation Moriah Towuntu Southeast Minahasa of Regency - Mandalele, Jenins Boy; Ratag, Patricia Linda (Abdurrauf Science and Society, 2025)
Indonesia is a developing country with a large population and still faces the complex problem of poverty. In Southeast Minahasa Regency, North Sulawesi Province, the poverty rate ranks eighth highest, and this issue is influenced not only by economic factors but also by cultural patterns, lifestyle, and spirituality. This research aims to explore the causes of poverty within the Evangelical Christian Church in Minahasa (GMIM) Moria Towuntu using a qualitative exploratory approach. Data were collected through a snowball sampling technique involving ten families who received social assistance. The results reveal three main causes of poverty: early-age marriage, inherited poverty culture from parents, and laziness. Moreover, from the perspective of Christian faith, poverty is understood as a consequence of structural sin and the family's weak spirituality in practicing Christian values. The inheritance of spiritual values is seen as a key to social transformation, where changes in culture, lifestyle, and spiritual orientation can lead to freedom from poverty. The Church is expected to actively serve as an agent of transformation, guiding its members from poverty toward an abundant life in Christ.